Perception of Musical Emotion in the Students with Congenital and Acquired Hearing Loss - mazaheryazdi, malihah; Aghasoleimani, Mina; Karimi, Mayam; arjmand, Pirooz (Iranian Journal of Child Neurology, 2018)
Objective Hearing loss can affect the perception of emotional reaction to the music. The present study investigated whether the students with congenital hearing loss exposed to the deaf culture, percept the same emotion from the music as students with acquired hearing loss. Materials & Methods Participants were divided into two groups; 30 students with bilaterally congenital moderate to severe hearing loss that were selected from deaf schools located in Tehran, Iran and 30 students with an acquired hearing loss with the same degree of hearing loss selected from Amiralam Hospital, Tehran, Iran and compared with the group of 30 age and gender-matched normal hearing subjects served our control in 2012. The musical stimuli consisted of three different sequences of music, (sadness, happiness, and fear) each with the duration of 60 sec. The students were asked to point to the lists of words that best matched with their emotions. Results Emotional perception of sadness, happiness, and fear in congenital hearing loss children was significantly poorly than acquired hearing loss and normal hearing group (P<0.001). There was no significant difference in the emotional perception of sadness, happiness, and fear among the group of acquired hearing loss and normal hearing group (P=0.75), (P=1) and (P=0.16) respectively. Conclusion Neural plasticity induced by hearing assistant devises may be affected by the time when a hearing aid was first fitted and how the auditory system responds to the reintroduction of certain sounds via amplification. Therefore, children who experienced auditory input of different sound patterns in their early childhood will show more perceptual flexibility in different situations than the children with congenital hearing loss and Deaf culture